A primary reference method for the characterization of Cd, Cr, Cu, Ni, Pb and Zn in a candidate certified reference seawater material: TEA/Mg(OH)2 assisted ID3MS by triple quadrupole ICP-MS/MS - Ari, Betul; Bakirdere, Sezgin (ELSEVIER, 2020)
A certified reference seawater material (CRM), UME CRM 1206 which was sampled from the Marmara Sea (40 31,423 N; 027 11, 333 E) with 27 psu of salinity is about to be released by Inorganic Analysis Laboratory of TuBI_TAK National Metrology Institute (UME). This paper represents the characterization measurements of Cd, Cr, Cu, Ni, Pb and Zn in this CRM. The use of a reference method by a single laboratory is one of the options for the characterization of a candidate CRM according to ISO 17034 [39]. This approach is used throughout this study with an introduction of a primary reference method. For this purpose, combination of triethylamine assisted Mg(OH)(2) co-precipitation and triple isotope dilution mass spectrometry (TEA/Mg(OH)(2)-ID3MS) were developed and validated. This optimized co precipitation protocol provided the recovery of target analytes within the range of 72%-92% which was the main advantage of TEA/Mg(OH)(2) method especially for Cd, Ni, Cu and Zn compared to NH4OH assisted co-precipitation. Analytical performance of TEA/Mg(OH)(2)-ID3MS were investigated under the optimum conditions. The results for matrix certified reference material were found to be not significantly different from the certified values based on the comparison of the results and certified values within their combined uncertainties. On the other hand, intermediate precision and repeatability of the developed method were found to be in the range of 0.34%-0.90% and 0.09%-0.49%, respectively. This study reports characterization measurements with their expanded uncertainties (k = 2) as 0.4327 0.0071 ng/g for Cd, 2.442 +/- 0.033 ng/g for Cr, 1.018 +/- 0.012 ng/g for Cu, 4.568 +/- 0.037 ng/g for Ni, 1.068 +/- 0.016 ng/g for Pb and 8.521 +/- 0.075 ng/g for Zn where the intermediate precision was found to be the main contributor to measurement uncertainty budget of TEA/Mg(OH)(2)-ID3MS method for each analyte. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: Triple isotope dilution mass spectrometry; Seawater; Trace elements; Triethylamine; Co-precipitation; Triple quadrupole ICP-MS/MS; PLASMA-MASS SPECTROMETRY; SOLID-PHASE EXTRACTION; DETECTOR DEAD-TIME; TRACE-ELEMENTS; METALS; PRECONCENTRATION; MS; GEOTRACES; MN; FE; Chemistry